ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI BENGKEL KONSENTRASI KEAHLIAN TEKNIK MEKANIK INDUSTRI (TMI) SMK NEGERI 2 SUKOHARJO - Rizqika Arung Pratama; Ngatau Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2025)
Occupational health and safety is a crucial aspect that needs to be studied and implemented. This research aims to analyze the level of knowledge and application of OHS by 12th-grade students majoring in Industrial Mechanical Engineering at SMK Negeri 2 Sukoharjo during their practical activities in the machining workshop. This study uses quantitative descriptive research supported by observations and interviews. The sampling technique uses the total sampling method. Data collection techniques include multiple-choice tests, direct observation, and interviews. The instrument validation technique uses content validation by experts. Quantitative data analysis techniques use assessment criteria. The results of this study indicate the knowledge of 12th-grade students in the Industrial Mechanical Engineering concentration at SMK Negeri 2 Sukoharjo, conducted through multiple-choice tests and observations based on 7 indicators. These indicators are knowledge of OHS scope, knowledge of OHS facilities and infrastructure, knowledge of work hazards, knowledge of Personal Protective Equipment (PPE), personal hygiene and health, workplace cleanliness and health, and ergonomics knowledge. All 7 indicators fall under good criteria. Observation results related to the implementation of OHS by 12th-grade students in the Industrial Mechanical Engineering concentration at SMK Negeri 2 Sukoharjo are based on 5 indicators. These indicators are: use of PPE, compliance with procedures, safe behavior during practice, implementation of 5S, communication and cooperation. The implementation of these 5 indicators is already good. Interview results show that the implementation of OHS during practice is already good. Keywords: Knowledge, Application, Occupational Health and Safety